Mulheres rurais no discurso da FAO: apagamentos, reconhecimentos, direitos e políticas públicas - Moura, Priscila Kavamura Guimarães de (2019)
I aim to analyze through this work the discourse of international organizations, especially the Food and Agriculture Organization of the United Nations (FAO), regarding rural women, based on a decolonial feminist theory. Using the qualitative methodology, the bibliographical survey, and the collection and interpretation of data throughout this work, I started the research by analyzing the various feminist currents, taking as reference the year 1948, moving to the current slopes. From then on, I explored the influence of these discussions in the context of international organizations, and how these thoughts shaped each other. This was mainly reflected in the proposals for women's insertion in the "Women in Development" and "Gender and Development" strategies, which aimed at converging the struggles for equal rights between men and women in the global and liberal development landscape. From this, I traced, historically and critically, the internalization of feminist debates in the discourses of international organizations. In the second part of the research I investigated certain FAO publications that had rural women as subjects and their gender policy. I sought to understand how this discourse assimilated the feminist proposals in vogue, what economic and social aspects, especially in a context of decolonial and postcolonial feminist critique inserted a theoretical context of the capitalist world-system. This implied to problematize the proposals of effectiveness of rights, insertion in the market, and stimulus to public policies taking as a reference the interests and peculiarities of the women who were not European or North American. Would there be coloniality within the proposals made by FAO?